2014
DOI: 10.1111/ecog.00908
|View full text |Cite
|
Sign up to set email alerts
|

Increasing temperature may compensate for lower amounts of dead wood in driving richness of saproxylic beetles

Abstract: Global warming and land‐use change are expected to be additive threats to global diversity, to which insects contribute the highest proportion. Insects are strongly influenced by temperature but also require specific habitat resources, and thus interaction between the two factors is likely. We selected saproxylic beetles as a model group because their life cycle depends on dead wood, which is highly threatened by land use. We tested the extent to which higher temperatures compensate for the negative effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
95
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 64 publications
10
95
1
1
Order By: Relevance
“…Saproxylic insects are strongly influenced by temperature but also they require specific dead wood features, and thus an interaction between the two factors appears likely. Observations and experimental data corroborate that an increasing temperature compensates at least partly for the lower amount of dead wood (Müller et al 2015).…”
Section: Discussionsupporting
confidence: 62%
“…Saproxylic insects are strongly influenced by temperature but also they require specific dead wood features, and thus an interaction between the two factors appears likely. Observations and experimental data corroborate that an increasing temperature compensates at least partly for the lower amount of dead wood (Müller et al 2015).…”
Section: Discussionsupporting
confidence: 62%
“…In a temperate forest of America, Reed and Muzika (2010) even suggested that slope aspect has little influence on the abundance and species richness of scolytid bark beetles. However, in a recent study executed in a temperate forest of southern Germany, it was suggested that flight intercept traps caught significantly higher numbers of species and individuals of saproxylic beetles in stands on warmer south-facing slopes than in those on colder north-facing slopes (Müller et al 2014). In the present study, the species richness of saproxylic beetles did not vary between WSS and CNS.…”
Section: Effect Of Topoclimatementioning
confidence: 94%
“…Ranius and Fahrig 2006;Lachat et al 2012). Especially, in a recent study, it was suggested that the amount of dead wood may interplay with temperature to affect the species richness of saproxylic beetles (Müller et al 2014). However, at small scales, the amount or volume of dead wood may be a poor predictor for saproxylic species richness and abundance (Schiegg 2000;Gibb et al 2006;Götmark et al 2011).…”
Section: Effect Of Topoclimatementioning
confidence: 99%
“…In addition to the dead-wood resource, temperature is assumed to be a crucial driver of the diversity of saproxylic beetles (Lachat et al 2012, Vodka & Cížek 2013, Müller et al 2014). Higher summer temperatures may even compensate for lower dead wood amounts (Köhler 2014, Müller et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the dead-wood resource, temperature is assumed to be a crucial driver of the diversity of saproxylic beetles (Lachat et al 2012, Vodka & Cížek 2013, Müller et al 2014). Higher summer temperatures may even compensate for lower dead wood amounts (Köhler 2014, Müller et al 2014. Gärdenfors & Baranowski (1992) concluded that 70% of the Swedish red-listed saproxylic beetles living on oaks preferred sun-exposed habitat and only 16% preferred dense stands (while this was the opposite for beech-related species).…”
Section: Introductionmentioning
confidence: 99%